Deficits in low beta desynchronization reflect impaired emotional processing in schizophrenia - Csukly, Gábor; Farkas, Kinga; Marosi, Csilla; Szabó, Ádám (Schizophrenia research, 2016)
Empirical data from previous investigations showed that emotion processing is reflected in beta, and especially in low beta event related desynchronization (ERD) (i.e. a decrease in low beta power). While recognition of social information and emotion processing are impaired in schizophrenia, no previous study analyzed induced and evoked beta oscillations in patients with schizophrenia during emotion processing. Twenty-eight subjects with schizophrenia and twenty-seven healthy controls subjects were enrolled in the study. The two study groups did not differ in age, gender and education. Participants viewed positive, neutral and negative scenes selected from the International Affective Picture System (IAPS) while 128-channel EEG was recorded. A significantly weaker low beta ERD was detected in patients relative to controls for the negative stimulus condition in the right parieto-occipital and temporal regions. Patients with decreased beta ERD showed more prominent negative symptoms and more severe deficits in psychosocial functioning. Only in the control group stronger beta ERD was detected for the negative stimuli relative to positive and neutral stimuli in the same regions. Our major finding is that impaired emotion processing in schizophrenia is reflected in decreased low beta ERD and in the diminished differences between low beta ERD to negative and non-negative emotional stimuli. Furthermore, it was found that patients with decreased beta ERD show more prominent negative symptoms and more severe deficits in psychosocial functioning.